Silent information regulator 1 modulator resveratrol increases brain lactate production and inhibits mitochondrial metabolism, whereas SRT1720 increases oxidative metabolism. Issue 7 (9th February 2015) - Rowlands, Benjamin D.; Lau, Chew Ling; Ryall, James G.; Thomas, Donald S.; Klugmann, Matthias; Beart, Philip M.; Rae, Caroline D.
Abstract : Silent information regulators (SIRTs) have been shown to deacetylate a range of metabolic enzymes, including those in glycolysis and the Krebs cycle, and thus alter their activity. SIRTs require NAD + for their activity, linking cellular energy status to enzyme activity. To examine the impact of SIRT1 modulation on oxidative metabolism, this study tests the effect of ligands that are either SIRT‐activating compounds (resveratrol and SRT1720) or SIRT inhibitors (EX527) on the metabolism of 13 C‐enriched substrates by guinea pig brain cortical tissue slices with 13 C and 1 H nuclear magnetic resonance spectroscopy. Resveratrol increased lactate labeling but decreased incorporation of 13 C into Krebs cycle intermediates, consistent with effects on AMPK and inhibition of the F0 /F1 ‐ATPase. By testing with resveratrol that was directly applied to astrocytes with a Seahorse analyzer, increased glycolytic shift and increased mitochondrial proton leak resulting from interactions of resveratrol with the mitochondrial electron transport chain were revealed. SRT1720, by contrast, stimulated incorporation of 13 C into Krebs cycle intermediates and reduced incorporation into lactate, although the inhibitor EX527 paradoxically also increased Krebs cycle 13 C incorporation. In summary, the various SIRT1 modulators show distinct acute effects on oxidative metabolism. The strong effects of resveratrol on the mitochondrial respiratory chain and on glycolysis suggest that caution should be used in attempts to increase bioavailability of this compound in the CNS. © 2015 Wiley Periodicals, Inc.